INOVASI PEMBUATAN SABUN DARI MINYAK JELANTAH SEBAGAI SOLUSI PENGELOLAAN LIMBAH RUMAH TANGGA - Nyoman Sri Widari; Bellanov, Agrienta; Tentua, Aulia Patricia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Abstract: Ngulan Wetan Village in Pogalan Sub-district, Trenggalek, has significant potential from organic waste such as rice husks, sawdust, dry leaves, and corn husks. Unfortunately, this waste is often burned and not utilized properly, causing environmental pollution. Meanwhile, fuel prices like LPG and charcoal continue to rise. To address this issue, a team from the Industrial Engineering Department at Universitas Katolik Darma Cendika conducted training on making briquettes from organic waste. The training covered all production steps, from raw material collection to briquette molding and drying. The technology used is simple and based on local resources. As a result, participants were able to produce an average of 12 kg of briquettes per month, exceeding the initial target, with part of the production sold, increasing household income by 10–15%. The program also encouraged behavioral changes in waste management and raised awareness about renewable energy and environmental sustainability. Keywords​: ​​Soap,Waste Cooking Oil, Environment